Międzynarodowe programy kształcenia – nowy kontekst uczenia się i rozwoju nauczycieli - Rojek, Marcin (Kultura-Społeczeństwo-Edukacja, 2023)
This article presents part of the research results conducted as part of the project “Comparative study on functions of international programmes in Poland” (NCN, Sonata Bis, no. 2020/38/E/HS6/00048). These results concern the learning of teachers implementing international education programs in Poland. It was found that the Polish teacher education system does not include preparation for work in international schools, which places these schools outside the Polish system of pedagogical support and supervision. Therefore, teachers start working in international schools with the conscious intention of learning this specific professional function, they experience rather favourable learning conditions there and try to make optimal use of these conditions. The analysis of teachers’ experiences allowed to identify and initially characterize three levels of organizing teachers’ learning: school, national and international.